Molecular identification, phylogeny and antifungal susceptibilities of dematiaceous fungi isolated from human keratomycosis - Arumugam Mythili; Coimbatore Subramanian Shobana; Krisztina Krizsán; Anamangadan Shafeeq Hassan; Annanthode Balakrishnan Sangeetha; Mónika Homa; Tamás Papp; Raed Abdullah Alharbi; AyoubAl Othaim; Alaa Baazeem; Kanesan Panneer Selvam; Moorthy Kannaiyan; et al. (Elsevier, 2023)
Purpose: To investigate the dematiaceous fungal profile of patients with ocular mycoses attending a tertiary eye care hospital in Coimbatore, India Methods: The identification of dematiaceous fungus based on their morphology, their genotypes, and the measurement of the minimum inhibitory concentrations (MICs) using microdilution method of routinely used antifungal drugs were all compared. Results: A total of 148 dematiaceous fungi were isolated during a study period of 27 months. Isolates were confirmed as Curvularia spp. (n = 98), Exserohilum spp. (n = 32), Alternaria spp. (n = 14), Exophiala spp. (n = 2), Cladosporium sp. (n = 1) and Aureobasidium sp. (n = 1). Out of 50 well grown isolates characterized genotypically based on the amplification and sequencing of the ITS region of the ribosomal RNA gene cluster and subsequent BLAST analysis, Curvularia lunata (n = 24), C. aeria (n = 1), C. spicifera (n = 8), C. hawaiiensis (n = 1), C. maydis (n = 2), C. papendorfii (n = 2), C. geniculata (n = 3), C. tetramera (n = 2) and Exs. rostratum (n = 7) were identified. In vitro antifungal susceptibilities of the most tested dematiaceous isolates showed that voriconazole had a MIC50 of 0.25 μg ml−1, while amphotericin B had a MIC50 of 0.25 μg ml−1 for Curvularia spp. and Alternaria spp. Conclusion: Voriconazole proved to be the most effective drug against the pigmented filamentous fungi, followed by amphotericin B, itraconazole and econazole.